Physical environment and employee commitment: a moderating role of work autonomy. (26th April 2022) - Shenoy, Veena; Uchil, Rashmi
The purpose of this paper is to examine the impact of physical environment on employee commitment with a moderating role of work autonomy. The questionnaire was formed on the basis of previously validated methods. 269 employees from various information technology (IT) companies were interviewed. Confirmatory factor analysis (CFA) is used to establish the reliability and validity measurements and a moderated structural equation modelling (MSEM) is used to test the hypothesis. The result of the study showed an optimistic influence of work autonomy on physical environment and employee commitment. Since the study was undertaken in IT firms, the generalisation of the same across other sectors is not possible and therefore a scope for further studies. The research tries to bring a three dimensional model highlighting the importance of work autonomy combining physical environment and employee commitment.